Legal issue in affirmative action policy development - Hickey, Thomas J.; Reid, Sue Titus (1996)
"Since 1964, public administrators in the United States have been faced with the challenge of providing discrimination-free employment opportunities. To attain this goal, many employers have instituted affirmative action programs but the legal status of these highly controversial programs is unclear. This article provides a concise overview of the legal issues in affirmative action programs. It analyzes recent, statutory and case law developments in an effort to gain insight into the future of affirmative action programs"
Keywords: Public administration - United States; Public administration